Analisis Biaya Produksi Dengan Variabel Costing Dalam Menentukan Harga jual Emping Melinjo - Effendi, Yanto; Tambunan, Dennis Rydarto; Herlin, Herlin (Politeknik Raflesia Press, 2024)
The cost of producing emping melinjo using the variable costing method in 2023 is IDR. 496,225 per can and the planned profit is Rp. 148,877, the variable method is used to see the exact selling price and can group each cost incurred.The results of this research can make a positive contribution to Mrs. Ros's Emping Melinjo business, in determining the costs to be incurred, so that it can compete fairly and produce quality products.